2019
DOI: 10.1097/prs.0000000000005104
|View full text |Cite
|
Sign up to set email alerts
|

Flap Preconditioning with the Cyclic Mode (Triangular Waveform) of Pressure-Controlled Cupping in a Rat Model: An Alternative Mode to the Continuous System

Abstract: Background: Improving flap survival is essential for successful soft-tissue reconstruction. Although many methods to increase the survival of the distal flap portion have been attempted, there has been no widely adopted procedure. The authors evaluated the effect of flap preconditioning with two different modes (continuous and cyclic) of external volume expansion (pressure-controlled cupping) in a rat dorsal flap model. Methods: Thirty rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Random‐pattern skin flaps are convenient and are thus frequently used in plastic and reconstructive surgery (Dehdashtian et al, 2019; El Shaer et al, 2019). However, ischaemic necrosis of the distal flap portion is a major complication after flap operation that limits wider clinical application of skin flaps (Hong et al, 2019). The current understanding of flap survival suggests that inadequate blood supply and ischaemia–reperfusion injury are the primary causes of distal flap necrosis (Wu, Chen, et al, 2019; Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Random‐pattern skin flaps are convenient and are thus frequently used in plastic and reconstructive surgery (Dehdashtian et al, 2019; El Shaer et al, 2019). However, ischaemic necrosis of the distal flap portion is a major complication after flap operation that limits wider clinical application of skin flaps (Hong et al, 2019). The current understanding of flap survival suggests that inadequate blood supply and ischaemia–reperfusion injury are the primary causes of distal flap necrosis (Wu, Chen, et al, 2019; Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 31 There is growing body of evidence in small animal preclinical models on the impact of wound healing and skin expansion models that has demonstrated the stimulation of external suction on increased angiogenic and adipogenic potential. 10 , 12 , 13 , 16 , 19 , 31 , 33 External volume expansion has previously demonstrated an influence on histological structure of tissues, and has shown to increase adipogenic potential 10 , 17 in fat grafting, and potential utility in diabetic and radiation in small experimental animal models. 8 , 13 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…14 Other authors have reported similar findings of increased vascularity and improved flap survival in animal models when treated with external negative pressure. 15–19…”
Section: Current Evidencementioning
confidence: 99%
“…The most common pressure setting reported is −125 mm Hg, and both continuous and intermittent suction settings have been utilized. 12–16 The report time period of treatment also varies, with the most common length of treatment being 5–7 days before intervention. 12–16 We present our initial experience using ENPD in free ALT flap reconstruction of upper extremity defects.…”
Section: Current Evidencementioning
confidence: 99%